Variation of physical activity during congested and non-congested periods in top-class European team season 2011-12 - Djaoui, L.; Dellal, A.; Pialoux, V.; Hautier, C. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
In modern elite soccer, the ability to recover from consecutive official match-play is considered as a key factor, especially during a congested period. However, to the best of our knowledge, no study has investigated how consecutive match-play influences the physical activity. Therefore, the aim of the present study was to examine the variation of physical activity of elite soccer players within a prolonged period of fixture congestion and non-congestion period (from August to December) in competitive season. Methods: 16 international players (24.3 ± 3.2 years; 178.1 ± 4.2 cm; 76.9 ± 4.3 kg), classified into 6 positional roles were examined during French First League and Cup (n=10) and UEFA Champion`s League (n=4) matches, in season 2011-2012 (central defenders: CD, n=3; full-backs: FB, n=2; central defensive midfielders: CDM, n=3; wide midfielders: WM, n=3; central attacking midfielders: CAM, n=2; forwards: FW, n=3). The total distance covered at light (<12 km/h), moderate (18 to 21 km/h), high (21 to 23 km/h), very high (23 to 25 km/h), over high (25 to 27 m/h), and sprinting (>27 km/h) intensity running were analyzed using a semi-automatic match analysis system (Amisco©). Results: No differences between congested and non-congested period for the total distance covered in all the speed thresholds superior at 18 km.h-1 were observed, whereas at light-intensity running, CD and CDM covered lower distance when playing 1 match/week (vs. 2 matches/ week, p<0.05). Moreover, no physical seasonal variation was found across all matches of the different periods analyzed from August to December. However, lower coefficient of variation were found concerning the overall distance and at light intensity (4.9-7.3%) in comparison with the others speed thresholds all across the playing positions. Furthermore, differences (p<0.001) were found among positions for verall distance covered (CDM=CAM > others), sprinting (FB > CD=CDM=CAM and WM=FW > CDM), over high (FB > CD=CDM & WM=CAM > CDM), very high (FB=WM=FW > CD=CDM), high (FB=WM=CAM=FW > CD=CDM), moderate (CAM > FB=CD=WM > CD) and light (CD=CDM > FB=WM=FW) intensities. Discussion: The present study reveals that the recovery time between two matches (72 to 96 hours) should not affect the physical performance during a prolonged period of fixture congestion in top-class soccer players. It could be suggested that post-match strategies (alternating legs` hot and cold water immersion, massage, diet and drink supplementation), and training including recovery and prevention session between matches, allow to reduce the apparition of fatigue and thus, to maintain sufficiently a high-level of physical performance within congested period.